Elective cardiovascular care in the era of the COVID-19 pandemic: managing tragic choices. Issue 3 (28th September 2020) - Berman, Adam E; Miller, Douglas; Sorrentino, Robert A; Mossialos, Elias A
Abstract : The COVID-19 pandemic has led to significant morbidity and mortality globally. As health systems grapple with caring for patients affected with COVID-19, cardiovascular procedures that are deemed 'elective' have been postponed. Guidelines concerning which cardiac procedures should be performed during the pandemic vary by specialty and geography in the USA. We propose a clinical heuristic to guide individual physicians and governing bodies in their decision making regarding which cardiac procedures should be performed during the COVID-19 pandemic using the behavioural economics concept of heuristics and ecological rationality.